2016
DOI: 10.4293/jsls.2016.00068
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transcystic Treatment Biliary Calculi by Laser Lithotripsy

Abstract: Background and Objectives:Laparoscopic transcystic common bile duct exploration (LTCBDE) is a complex procedure requiring expertise in laparoscopic and choledochoscopic skills. The purpose of this study was to investigate the safety and feasibility of treating biliary calculi through laparoscopic transcystic exploration of the CBD via an ultrathin choledochoscope combined with dual-frequency laser lithotripsy.Methods:From August 2011 through September 2014, 89 patients at our hospital were treated for cholecys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…However, there are major methodological differences between these studies and the study we present here, making direct comparison difficult. One study excluded patients if the transcystic route was not possible [28], and another study excluded patients presenting acutely with cholecystitis and obstructive jaundice or having failed ERCP [16]. These factors most likely decrease the complexity of reported cases in previous cohorts compared to the present study, which included patients with acute presentations and those requiring TD LCBDE.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, there are major methodological differences between these studies and the study we present here, making direct comparison difficult. One study excluded patients if the transcystic route was not possible [28], and another study excluded patients presenting acutely with cholecystitis and obstructive jaundice or having failed ERCP [16]. These factors most likely decrease the complexity of reported cases in previous cohorts compared to the present study, which included patients with acute presentations and those requiring TD LCBDE.…”
Section: Discussionmentioning
confidence: 94%
“…The use of laser lithotripsy as an adjunct to LCBDE was first described in a small five-patient case series, which demonstrated efficacy even when faced with large and/or impacted ductal calculi [13,17]. Subsequently, larger studies have reported its safety and efficacy, demonstrating no associated increase in biliary related or other complications [15,16,28,29]. Results from this study have comparable rates of duct clearance to these larger series but suggest that there is a small but significant increase in the rate of post-operative bile leak with LABEL cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Despite of its several advantages, transcystic management also has some disadvantages such as cannulation difficulty, transition to choledochotomy in large stones, [8,15] and lithotripsy. [16] Some authors consider the transcystic approach as risky in stones of larger than 20 mm. [17] There is no unanimous opinion regarding the completion of choledochotomy with T-drainage, primary suture or stend, which is another issue of laparoscopic choledochotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Literature recommends lithotripsy and abdominal lithotripter tools for removal of riveted stones. [16,25] Our study has a number of limitation, which include non-randomization of groups, and failure to provide dimensions of stones and choledoch.…”
Section: Discussionmentioning
confidence: 99%